Implementasi Gripper Pada End Effector Robot Untuk Memegang Telur Ayam Dengan Sensor FSR (Force Sensitive Resistor) - Alfian Reza Pahlevi; Dahnial Syauqy; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Robots with gripper can help users to grab objects in a place that is unattainable to humans. Users also do not need to directly interact with the object directly because the robot can be controlled wirelessly with the help of wifi and Android devices. As a substitute for the senses of taste on human skin is used FSR sensor (Force Sensitive Resistor). This sensor is used to obtain the value of the gripper's closeness when grabbing the object. To overcome the damage of the object, the gripper is implemented can stop automatically by using the threshold value. The threshold used is 552. The value of 552 is obtained from the average result on the 10 data acquisition of sensor values ​​using the FSR sensor with manual experiment. When the value of the sensor obtained through the threshold, then the robot gripper will automatically stop. This is done to prevent damage to the chicken egg object. From the test as much as 10 times on the robot gripper, obtained test results with 100% percentage that the system can stop gripper and chicken egg object is not damaged. From the test results obtained different pressure values ​​on each object. This may be due to layers of chicken egg object is different or the value of the sensor that keeps changing.